Philippine medical thesaurus on anatomy musculoskeletal system - Hofileña, Joan Carlin Marie A. (2003)
The uncontrollable growth of information specifically in the field of Medicine, as a result of years of data acquisition raises a need for information management. Medicine, a distinct discipline due to the technicality and preciseness of terms, usually faces issues of vagueness and ambiguity in medical terms. The need for an effective tool to coordinate these terms and to promote efficiency in storage and information dissemination is highly acknowledged in this study.